Methodology proposal for a new approach in the study of the Peruvian electoral process through public opinion surveys - Huamanchumo de la Cuba, Luis (2003)
In the 1920s Lima was conceived as a utopian Europe and "old world" architectural styles were transplanted to this city. to represent, paradoxically, the "new homeland" The last decades of Lima under English colonial influence and the beginning of a new stage of domination sinceUSA. They were expressed in a varied and fanciful Lima architecture. It was in the Lima home, especially in the "chalet" that this phenomenon had its maximum expression.We verified this in the neighborhood of Santa Beatriz (1921-1930)); Through a sample of 53 homes obtained from the Archive of the Ministry of Public Works, it is discovered that the residential architecture of this neighborhood, both single-family housing and collective housing, It was conceived by architects - I mean the first construction architects of Peru - and engineers.